An Investigation into Some Typical Linguistic Factors Causing Laughter in British Funny Stories. M.A Thesis Linguistics: 60 22 15 - Nguyễn, Thị Kim Phương (University of Languages and International Studies, 2017)
This thesis is an attempt to uncover humour creating ways in British funny stories from linguistic perspective. It provides learners of English with better understanding of English jokes and funny stories. To accomplish this research, the theoretical backg (...)